Ablation strategies for different types of atrial fibrillation in Europe: results of the ESC-EORP EHRA Atrial Fibrillation Ablation Long-Term registry. Issue 4 (10th December 2019) - Schmidt, Boris; Brugada, Josep; Arbelo, Elena; Laroche, Cécile; Bayramova, Sevda; Bertini, Matteo; Letsas, Konstantinos P; Pison, Laurent; Romanov, Alexander; Scherr, Daniel; Tilz, Roland Richard; Maggioni, Aldo; et al.
Abstract: Aims: The ESC EORP EHRA Atrial Fibrillation (AF) Ablation Long-Term registry was designed to assess management and outcomes of AF catheter ablation procedures in Europe. To investigate the current ablation approaches and their outcomes for patients with paroxymal AF (PAF) and non-PAF in Europe. Methods and results: Data from index ablations were collected in 27 European countries at 104 centres in a prospective fashion. Pre-procedural, procedural, and 1-year follow-up data were captured on a web-based electronic case record form. Data on the ablation procedure were available for 3446 patients. Of these, 2513 patients and 933 patients underwent pulmonary vein isolation (PVI) or PVI plus (PVIplus) additional ablation, respectively. The ablation strategy was limited to PVI in 81% and 56% of patients in the PAF and non-PAF group, respectively ( P  < 0.001). In the non-PAF group, left atrial linear ablation and ablation of complex fragmented atrial electrograms were more commonly performed. Arrhythmias recurrence after PVI was 29% and 39% in the PAF and non-PAF group, respectively ( P  < 0.001) and 42% after PVIplus in both groups. Atrial fibrillation related hospital admissions were more common in the PVIplus group (20% vs. 14%). A very low procedural complication rate was observed. No relevant differences were observed with regard to repeat ablation (PVI 9% and PVIplus 11%). Conclusion: In patients with PAF and non-PAF, the ablation strategies of PVI and PVIplus led to similar arrhythmia-free survival rates after 1 year. A considerable hospital readmission rate was noted.